2020
DOI: 10.1002/ange.201915876
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of (−)‐Pepluanol B: Conformational Control of the Eight‐Membered‐Ring System

Abstract: The first total synthesis of the Euphorbia diterpenoid pepluanol B in both racemic and enantioenriched form involves 20 steps from a known bicyclic diol. This synthesis features an unprecedented bromo‐epoxidation to control the eight‐membered‐ring conformation. In addition, salient reactions for the construction of the tetracyclic backbone include a sterically challenging aldol reaction to establish the quaternary center, a ring closing metathesis (RCM) to forge the eight‐membered ring, and a diastereoselectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Another elegant example of conformational design in medium rings was disclosed by She and co-workers very recently in the total synthesis of (À)-pepluanol B (Scheme 19), [52] which was associated with conformationally controlled methylation of cyclooctanone.I nsight into the LEC by NMR spectroscopy and X-ray crystallography showed that the C14 carbonyl group in 19-1 adopted an upward orientation almost parallel to the C7 À OH group,t hen MeI approached from the backward direction of the stereospecific Z-enolate intermediate (Int-I), thus yielding the undesired (13S)-19-2.C onsidering the C14 carbonyl orientation might be affected by the C7 tertiary alcohol through intramolecular hydrogen bonding,the authors used abromo-epoxide moiety to eliminate this interaction, and thus changed the conformation of the cyclooctanone ring. Finally,when the substrate 19-3 bearing aC 14 carbonyl with an inverse orientation was used, the desired methylation proceeded smoothly through a Z-enolate intermediate (Int-II)t oa fford the desired product 19-4 in good yield.…”
Section: Medium-and Large-ring-type Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another elegant example of conformational design in medium rings was disclosed by She and co-workers very recently in the total synthesis of (À)-pepluanol B (Scheme 19), [52] which was associated with conformationally controlled methylation of cyclooctanone.I nsight into the LEC by NMR spectroscopy and X-ray crystallography showed that the C14 carbonyl group in 19-1 adopted an upward orientation almost parallel to the C7 À OH group,t hen MeI approached from the backward direction of the stereospecific Z-enolate intermediate (Int-I), thus yielding the undesired (13S)-19-2.C onsidering the C14 carbonyl orientation might be affected by the C7 tertiary alcohol through intramolecular hydrogen bonding,the authors used abromo-epoxide moiety to eliminate this interaction, and thus changed the conformation of the cyclooctanone ring. Finally,when the substrate 19-3 bearing aC 14 carbonyl with an inverse orientation was used, the desired methylation proceeded smoothly through a Z-enolate intermediate (Int-II)t oa fford the desired product 19-4 in good yield.…”
Section: Medium-and Large-ring-type Substratesmentioning
confidence: 99%
“…[53] Scheme 19. Total synthesis of pepluanol Bg uided by conformational design by She and co-workers [52] (DDQ = 2,3-dichloro-5,6-dicyano-1,4benzoquinone, TPAP = tetrapropylammonium perruthenate, NMO = 4methylmorpholine N-oxide).…”
Section: Medium-and Large-ring-type Substratesmentioning
confidence: 99%
“…[72] In parallelt ot he isolation and biology studies, extensive and growing synthetic efforts have been devoted to this group of terpenoids. [73] In this context, our group targeted somes tructurally novel members and recently achieved the first total synthesis of pepluanol B, [74] that containsadiquinane core embedded in the novel tetracyclic carbon architecture.I no rder to improve the synthesis efficiency,w ed ecided to introduce the diquinaned omain in early stage, thereby, utilizedaC 2 -symmetric bicyclicd iol 146 as our synthetic precursor,w hich in turn can be readily prepared on large scale from commerciallya vailable cycloocta-1,5-diene 145 through aP d-catalyzed transannularc arbocyclization and ah ydrolysis reaction. [75] This two-stepp rotocol only required one-columnp urification.…”
Section: Euphorbia Terpenoid Pepluanol Amentioning
confidence: 99%
“…In a systematic research of the phytochemical ingredients of E. peplus , a traditional medicine collected from southwestern China, the Qiu group has identified five novel diterpenoid compounds named pepluanols A–D and pepluacetal (Figure c) . Significantly, these molecules are Kv1.3 inhibitors and thus serve as potential agents to treat autoimmune diseases, resulting in two synthetic approaches on pepluanol A ( 8 ) from the Ding and Gaich groups , and one on pepluanol B ( 9 ) from our group …”
mentioning
confidence: 99%
“…We noticed that the C14 carbonyl adopts a downward orientation in the three-dimensional conformation of pepluanol B . Thus, the bridgehead C7 tertiary alcohol C–O bond is parallel to the C14 carbonyl in “head-to-tail” form, which might provide some hyperconjugation effect to the conformational stability.…”
mentioning
confidence: 99%